2017
DOI: 10.1002/acm2.12140
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic analysis of Intrabeam‐based intraoperative radiation therapy in the treatment of unicentric breast cancer lesions utilizing a spherical target volume model

Abstract: It is postulated that the outcomes in treating breast cancer with intraoperative radiotherapy (IORT) would be affected by the residual cancer cell distribution within the tumor bed. The three‐dimensional (3D) radiation doses of IntrabeamTM (IB) IORT with a 4‐cm spherical applicator at the energy of 50 and 40 kV were calculated. The modified linear quadratic model (MLQ) was used to estimate the radiobiological responses of the cancer cells and interspersed normal tissues with various radiosensitivities. By comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…After acquiring the measured depth doses by using an ionization chamber type PTW 34013 on water phantom in our previous study [32], the second step was the validation of the simulation procedure used in the present study by comparing the simulation with the measured depth dose profiles. The relative dose shown in figures 5(a) and (b) drops exponentially because the energy used was low kV (50 kV) and this shows a better conformity with the half-Gaussian cancer cell distribution in the tumor bed [58]. Additionally, the results in figures 5(c) and (d) show that, in all of the cases, the gamma indexes were below 1.…”
Section: Discussionmentioning
confidence: 72%
“…After acquiring the measured depth doses by using an ionization chamber type PTW 34013 on water phantom in our previous study [32], the second step was the validation of the simulation procedure used in the present study by comparing the simulation with the measured depth dose profiles. The relative dose shown in figures 5(a) and (b) drops exponentially because the energy used was low kV (50 kV) and this shows a better conformity with the half-Gaussian cancer cell distribution in the tumor bed [58]. Additionally, the results in figures 5(c) and (d) show that, in all of the cases, the gamma indexes were below 1.…”
Section: Discussionmentioning
confidence: 72%
“…However, in recent years, mobile IORT with low voltage (about 20 to 50 kV) such as INTRABEAM (Carl Zeiss AG, Germany) and electronic brachytherapy system Axxent (Fremont, California Xoft Inc.) gained significant popularity in IORT field [30]. These systems harbor gradient radiation slope and do not require special protection equipment and its applicators are sphere shape with different sizes and seldom infiltration depth (0.5 to 1 cm), thus making these devices a proper tool for targets with sphere shapes, or in spherical cavities [31].…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, Fowler 22 suggested an α/β ratio of around 4 Gy as an approximation of breast cancer’s radiobiological response. In 2003 Guerrero and Li 21 found some breast cancer cells still have an α/β of 10 Gy with an α of 0.3 Gy −1 , a β of 0.03 Gy −2 , and a half‐life repair time of 1 h. In 2017 Schwid et al 23 found the breast cancer treatment can benefit from a nonuniform dose field radiotherapy regardless of their radiosensitivity. In this study, both of these breast cancer cell lines (α/β = 4 and 10 Gy) were used and respectively named as the acutely responding breast cancer (C1, α/β = 10 Gy) and the slowly responding breast cancer (C2, α/β = 3.846 Gy).…”
Section: Methodsmentioning
confidence: 99%